A Case of Recurrent Anaplastic Meningioma of the Skull Base with Radiologic Response to Hydroxyurea - Gurberg, Joshua; Bouganim, Nathaniel; Shenouda, George; Zeitouni, Anthony (Journal of Neurological Surgery Reports, 2014)
Anaplastic meningiomas are rare and aggressive tumors with a high propensity for local recurrence. Surgical resection and postoperative radiotherapy are the standard of care for primary disease and local recurrences. Refractory disease is managed with chemotherapy with limited success. A highly efficacious, well-tolerated chemotherapeutic agent has yet to be found for this disease entity. Hydroxyurea is currently receiving renewed attention because of its efficacy in inducing apoptosis of meningioma cells in vitro and its favorable side-effect profile. Thus far, in humans, this agent has only induced stable disease.We describe the first patient showing a near complete/partial clinical and radiological regression after 5 months of 25 mg/kg of hydroxyurea once daily, given within 1 month after stereotactic fractionated reirradiation of a previously irradiated and operated anaplastic meningioma of the skull base. Magnetic resonance imaging showed a significant and sustained response with tumor shrinkage and cavitation.
Keywords: meningioma; anaplastic meningioma; hydroxyurea; radiotherapy; recurrent; malignant transformation